Structural Analysis In The Fairy Tale “Hänsel”Und Gretel” And “Golden Cucumbers” - Siahaan, Dhela Adinda R.P; Purba, Lydia; Simanjuntak, Tarida Alvina (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to describe the structure of the fairy tales "Hänsel und Gretel" and "Timun Emas" using Marquaβ's structural theory. The theory used in this study is Marquaβ's structural theory. The data sources for this study are the fairy tales "Hänsel und Gretel" by Brüder Grimm and "Timun Emas" by Rahma Asa. The data were analyzed using qualitative descriptive techniques. The results of this study are as follows: 1) both fairy tales have structures that follow the basic fairy tale pattern with a progressive plot containing conflict, peak tension, and a satisfying resolution. 2) the main characters in both stories have brave and clever characters even though Hänsel and Gretel appear as a duo with complex interactions, while Timun Emas is more prominent as a single, independent character. 3) the dominant setting is a forest which symbolizes trials and changes in fate, while the time setting is symbolic and supports the atmosphere of the story. 4) the point of view used is third person, providing a broad and objective narrative. This study enriches the study of fairy tale structural literature.